Analysis of Recruitment and Empowerment and Their Influence on the Human Resources Performance of the Nganjuk Environmental Service - Irawan, Roynaldi Wahyu; Sugiono, Sugiono (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of the research is understand the recruitment process to distribute employees evenly so that the strength of human resources becomes more balanced. Design/Method/Approach: This method uses a quantitative approach with associative causality research techniques. In this research, the questionnaire uses the SPSS application in the calculation process. Research Findings Research Finding: The results of multiple regression analysis show that Recruitment (X1) and Human Resource Empowerment (X2) partially influence the dependent variable (Y), namely Employee Performance. Meanwhile, the Ha test simultaneously means that Recruitment (X1) and Human Resource Empowerment (X2) as a whole (simultaneous) have an effect on the dependent variable (Y) on Human Resource Performance. Theoretical contribution/originality: Human resource planning has a significant and positive effect on HR performance, according to HR planning it turns out to have an effect on employee performance, although not significant. Research Limitations: In this research, by limiting the problem to variables, this research only focuses on discussing recruitment and empowerment of human resources for managing employee performance at the Environmental Service.